HUBUNGAN PERSEPSI IBU HAMIL TENTANG VAKSINASI COVID 19 DENGAN MINAT IBU HAMIL DALAM MENGIKUTI VAKSINASI: The Relationship between the perception of pregnant women about the covid-19 vaccination with the interest of pregnant women in participating in the vaccination - Hidayati, Tutik; Ekasari, Tutik (LPPM - STIKES Pemkab Jombang, 2023)
Covid-19 is a group of viruses that can cause disease in animals or humans. Several types of corona viruses are known to cause respiratory tract infections in humans ranging from coughs and colds to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). This study aims to analyze the relationship between pregnant women's perceptions of Covid 19 vaccination with pregnant women's interest in taking vaccinations in the Tongas Health Center, Probolinggo.This research is a quantitative research design with a correlational design using a cross sectional study approach with 35 respondents. Data collection includes coding, editing and tabulating, then analyzed manually and computer with Chi Square Test. According to the study's findings, out of 35 respondents, the majority of pregnant women had positive opinions of the COVID 19 vaccination, according to 23 respondents (65.7%), including the interest of pregnant women in receiving the vaccination, which was expressed by 21 respondents (60%) while those who were uninterested were represented by 2 respondents. (5.7%). Pregnant women's perceptions of the Covid 19 immunization and their desire in receiving vaccinations at the Tongas Health Center in Probolinggo Regency are related, as indicated by the obtained P Value of 0.001 and a = 0.05, which suggests that H0 is rejected and Ha is accepted. It is hoped that the screening process for targeting pregnant women should be carried out in detail and thoroughly. For pregnant women, the screening or screening process must be carried out in detail compared to other targets. The thing to remember is that giving the COVID-19 vaccine does not fully protect pregnant women from the Corona virus